2014
DOI: 10.2466/08.cp.3.22
|View full text |Cite
|
Sign up to set email alerts
|

Metric invariance of the French version of the Contingencies of Self-Worth Scale1,2,3

Abstract: The Contingencies of Self-Worth Scale is a self-report questionnaire assessing seven types of 'reward' for self-worth. To test its construct validity, the French version was administered to 787 undergraduate students of both sexes and the data submitted to confi rmatory factor analyses (CFA) with the robust MLM or WLSMV estimators. The reliability of the 7-factor structure as well as its sex invariance were checked with the multiple-group factor model for orderedcategorical measures. The correlated 7-factor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, a review of the literature revealed that the hypothesized 7-factor model supported by failed to show a consistently good fit to the data in several successive studies (i.e., Bentea 2016;Kempenaers Enrico Perinelli and Guido Alessandri should be considered co-first authors. They contributed equally to this work and the order of their names was arbitrary.…”
mentioning
confidence: 99%
“…However, a review of the literature revealed that the hypothesized 7-factor model supported by failed to show a consistently good fit to the data in several successive studies (i.e., Bentea 2016;Kempenaers Enrico Perinelli and Guido Alessandri should be considered co-first authors. They contributed equally to this work and the order of their names was arbitrary.…”
mentioning
confidence: 99%